2018
DOI: 10.1186/s13019-018-0699-4
|View full text |Cite
|
Sign up to set email alerts
|

Case report of an unusual combination of purulent pericarditis and false aneurysm of the ascending aorta

Abstract: Background: Purulent pericarditis is an uncommon entity, which is, in very rare cases, associated to infection of the aorta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Purulent pericarditis is a rare, life‐threatening infection of the pericardial space that may initially elude diagnosis. Purulent pericarditis was more prevalent in the pre‐antibiotic era and was a feared complication of pneumococcal pneumonia . Although purulent pericarditis occurs in only an estimated 1 of 18 000 hospitalized patients, the progression can be very rapid, and half of all cases are diagnosed on autopsy .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Purulent pericarditis is a rare, life‐threatening infection of the pericardial space that may initially elude diagnosis. Purulent pericarditis was more prevalent in the pre‐antibiotic era and was a feared complication of pneumococcal pneumonia . Although purulent pericarditis occurs in only an estimated 1 of 18 000 hospitalized patients, the progression can be very rapid, and half of all cases are diagnosed on autopsy .…”
Section: Discussionmentioning
confidence: 99%
“…Aside from pulmonary parenchymal disease, purulent pericarditis is associated with other infections of the mediastinum and neck, such as empyema, mediastinitis from dental infection, intracardiac medical devices, eroding intrathoracic malignancies, and endocarditis and bacteremia . The microbiology of purulent pericarditis reflects this, with Staphylococcus , Streptococcus , Haemophilus , and Mycobacterium tuberculosis predominating, though atypical organisms such as Candida and Salmonella have been described.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial left/right shunting developed, leading to right heart decompensation with tricuspid regurgitation and liver congestion. Thus, it can be concluded that in case of high-risk pathogens such as Staphylococcus spp., clinicians should be aware that serious complications such as mycotic aneurysms 6 or even fistulas creating a hemodynamically relevant shunt may lead to life-threatening situations within a few days.…”
Section: Discussionmentioning
confidence: 99%